Low Molecular Weight Norbornadiene Derivatives for Molecular Solar‐Thermal Energy Storage. Issue 37 (5th August 2016) - Quant, Maria; Lennartson, Anders; Dreos, Ambra; Kuisma, Mikael; Erhart, Paul; Börjesson, Karl; Moth‐Poulsen, Kasper
Abstract: Molecular solar‐thermal energy storage systems are based on molecular switches that reversibly convert solar energy into chemical energy. Herein, we report the synthesis, characterization, and computational evaluation of a series of low molecular weight (193–260 g mol −1 ) norbornadiene–quadricyclane systems. The molecules feature cyano acceptor and ethynyl‐substituted aromatic donor groups, leading to a good match with solar irradiation, quantitative photo‐thermal conversion between the norbornadiene and quadricyclane, as well as high energy storage densities (396–629 kJ kg −1 ). The spectroscopic properties and energy storage capability have been further evaluated through density functional theory calculations, which indicate that the ethynyl moiety plays a critical role in obtaining the high oscillator strengths seen for these molecules. Abstract : Molecular solar‐thermal energy storage : A synthetic route to norbornadienes with a cyano acceptor and ethynyl‐substituted aromatic donor groups has been developed. The products have been used in low molecular weight norbornadiene–quadricyclane molecular switches with promising molecular solar energy storage properties (see graphic).